Clade Ia Monkeypox Virus Linked to Sexual Transmission, Democratic Republic of the Congo, August 2024 - Jean-Claude Makangara-Cigolo; Kelly-Michel Kenye; Lygie Lunyanga; Daan Jansen; Eddy Kinganda-Lusamaki; Sifa Kavira; Adrienne Amuri-Aziza; Emile Malembi; Yvon Anta; Prince Akil-Bandali; Emmanuel Lokilo-Lofiko; Emmanuel Hasivirwe Vakaniaki; et al. (Emerging Infectious Diseases)
Several concurrent mpox outbreaks are ongoing in the Democratic Republic of the Congo. We report a case of severe clade Ia mpox in an adult woman with indeterminate HIV status who died 16 days after symptom onset. She self-identified as a sex worker and had spent time in the capital city, Kinshasa.